DESCRIPTION OF TROMBOSITES IN POLISI DOGS AT THE STATE POLICE OF THE REPUBLIC OF INDONESIA, MALANG CITY RESORT - Holifatullah, Ahmad Rohmadhon; Utama, Iwan Harjono; Widyastuti, Sri Kayati (Buletin Veteriner Udayana, 2023)
A medical examination is a mandatory treatment received by police dogs to monitor health, that performance in the field becomes optimal. Regular blood tests are importance to get health information. Platelets are one of the importance indicators in the blood test results in the form of Platelet values (PLT), Mean Platelet Volume (MPV), Platelet Distribution Width (PDW), and Platelet Crit (PCT). This value can establish a diagnosis and become a health surveillance parameter in police dogs. This study is conduct observationally to determine the picture of platelets in police dogs in the Malang City Resort police. The sample came from all police dogs in the Malang City Resort Police, which amounted to 10 tails. Blood samples were read using the Haematology Analyzer RT-7600 machine in Clinical Pathology Laboratory at Brawijaya University. The result of the study showed that in the value of PLT, five police dog blood samples had thrombocytopenia and five others within the range of typical values. Only one specimen is below the range of expected values at the MPV value. At the PDW value, all samples are in the expected range value. On PCT value, all specimens are also in the normal range of values. It can conclude that the study of PLT values in 5 police dogs had thrombocytopenia in the MPV value of 1 sample below the normal range in addition to the PDW and PCT values of all specimens within the normal range. The need for follow-up platelet examinations such as liver and bone marrow biopsies for further check-ups. The addition of a routine blood check agenda on police dogs needs to be made.